REAL IMPLICATIONS OF CORPORATE RISK MANAGEMENT: REVIEW OF MAIN RESULTS AND NEW EVIDENCE FROM A DIFFERENT METHODOLOGY - Dionne, Georges; Mnasri, Mohamed (L'Actualité économique, 2018)
This study revisits the question of whether risk management has real implications on firm value, risk, and accounting performance using a new dataset on the hedging activities of U.S. oil producers. In light of the controversial results in the literature, this paper estimates the hedging premium question for firms by using a more robust econometric methodology, namely essential heterogeneity models, that controls for bias related to selection on unobservables and self-selection in the estimation of marginal treatment effects (MTE). We find that oil producers with higher propensity scores for the use of more extensive hedging activities tend to have higher marginal firm value and higher marginal risk reduction and realize stronger marginal accounting performance. These oil producers with higher propensity scores also have significant average treatment effects (ATE) for firm financial value, idiosyncratic risk and systematic risk.